SHORT TERM EFFECT OF ACUPUNCTURE-TENS ON LUNG FUNCTIONS AND DYSPNEA FOR SUBJECTS WITH MODERATE COPD (International Journal of Physiotherapy, 2015)
Background: Acupuncture TENS is used to improve pain instead of invasive acupuncture. Acupuncture shown to improve dyspnoea and lung functions in COPD (Chronic Obstructive Pulmonary Disease) patients. The purpose of the study is to determine Short term effectiveness of Acupuncture-TENS in reducing dyspnea and improving lung functions for subjects with moderate COPD.Method: An experimental study design, selected 30 geriatric subjects with COPD randomized 15 subjects into each Study and Control group. Study group received Acu-TENS for 45 minutes for total 5 sessions, while control group received placebo TENS. Outcome measurements such as breathlessness using Modified Borg Scale (MBS), Lung functions using Pulmonary Function Test (PFT) was measured before and after intervention.Results: Analysis from pre-intervention to post-intervention within study group found that there is statistically significant change in means of MBS, FEV1, FEV1/FVC ratio and within control group there is a statistically significant change in means of MBS, but there is no statistically significant change in means of FEV1, FVC and FEV1/FVC ratio. When post-intervention means were compared between the groups there is no statistically significant difference in means of MBS and FEV1, FVC and FEV1/FVC ratio.Conclusion: It is concluded that one week of Acu-TENS on EXL1 point found no significant effect on improving dyspnea and lung functions in subjects with moderate COPD in geriatric populations.